Green Disposable Packaging and Communication: The Implications of Bring-Your-Own-Container - Peng, Yunlong; Gao, Fei; Chen, Jian (Manufacturing and Service Operations Management, 2025)
Problem definition: A growing number of firms are encouraging consumers to participate in “bring-your-own-container” (BYOC) behavior in which consumers bring their own reusable packaging to purchase and consume products, thus reducing single-use packaging waste. In this paper, we study the environmental implications of a firm’s BYOC implementation when considering its disposable packaging choice and communication strategy. Methodology/results: We build a stylized model to study a firm’s joint decisions on BYOC, disposable packaging choice, and communication and their implications on the environment. Our main results follow. First, allowing BYOC reduces the firm’s incentive to make fraudulent green claims about its disposable product packaging; however, BYOC implementation may harm the overall environment while improving the firm’s profit, thereby creating a new form of greenwashing. Second, the adoption of third-party certification for green disposable packaging is an effective remedy to mitigate the negative environmental impact of BYOC. In addition, the environmental implications of adopting third-party certification (either voluntarily or because of government mandates) depend on the relationship between the environmental qualities of green disposable packaging and reusable packaging. Whereas it always benefits the environment when the firm’s green disposable packaging has better environmental performance, adopting certification may negatively impact the environment if consumers’ reusable packaging is greener. Furthermore, we find numerically that offering a price discount for BYOC may encourage the firm to adopt certification because of increased profitability, thereby leading to the aforementioned environmental implications. Managerial implications: We offer operational insights on how firms should make joint decisions on BYOC, disposable packaging choice, and communication. We also generate insights on how governments should regulate firms’ green claims when firms start to allow BYOC. Supplemental Material: The online appendix is available at https://doi.org/10.1287/msom.2021.0605 .